2011
DOI: 10.1007/s12011-011-9124-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shock Waves on Oxidative Stress, Antioxidant Enzyme and Element Levels in Kidney of Rats

Abstract: The aim of this study was to investigate the effect of extracorporeal shock wave lithotripsy (ESWL) on kidney oxidative stress and trace element levels of adult rats. Twelve male Wistar albino rats were divided equally into two groups. First group was used as control. The right-side kidneys of animals in second group were treated with 2,000 18-kV shock waves under anesthesia. Localization of the right kidney was achieved following contrast medium injection through a tail vein under flouroscopy control. The ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…This observed reduction in the activity of antioxidant enzymes under stress conditions is in agreement with earlier reports using a range of oxidative and other challenges [1,39,40,41], The increased production of ROS that results from oxidative stress leads to modifications in lipids, carbohydrates, proteins and nucleic acids, resulting in cytotoxicity and dysfunction in several tissues [42].…”
Section: Discussionsupporting
confidence: 92%
“…This observed reduction in the activity of antioxidant enzymes under stress conditions is in agreement with earlier reports using a range of oxidative and other challenges [1,39,40,41], The increased production of ROS that results from oxidative stress leads to modifications in lipids, carbohydrates, proteins and nucleic acids, resulting in cytotoxicity and dysfunction in several tissues [42].…”
Section: Discussionsupporting
confidence: 92%
“…In our work, we showed increased expression of inducible NO synthase (iNOS) and NF κ B, indirect evidence of increased OS [42]. Recently, Gecit et al showed that ESWL treatment produces OS and causes impairment in the antioxidant and trace element levels in the kidneys of rats [43]. ESWL is associated with greater prevalence of hypertension [44].…”
Section: Urinary Obstruction Urolithiasis Infection Ischemia Rementioning
confidence: 64%
“…SOD catalyzes the dismutation of the superoxide anion radical to water and hydrogen peroxide, which is detoxified by the CAT activity. Usually, a simultaneous induction response in the activities of SOD and CAT is observed when an exogenous antioxidant is applied 20, 21. Decreased tissue GSH‐Px activity in this study indicated that oxidation of GSH to GSSG is likely to be lowered by crush or axotomy of phrenic nerves.…”
Section: Discussionmentioning
confidence: 59%